1991
DOI: 10.1038/icb.1991.39
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the immune response by tachykinins

Abstract: Summary Neuro‐immunology is becoming an increasingly important discipline of immunology. This review has examined the immunomodulatory function of one group of neuropeptides, the TK, particularly SP and NKA. These peptides are localized in primary afferent nerves which have been shown to innervate several immune organs. In addition, binding sites for the TK have been demonstrated in thymus, spleen and lymph node. Several immune cell types also express neurokinin receptors including human circulating lymphocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 78 publications
1
24
0
Order By: Relevance
“…22 blasts, lymphocytes and macrophages are equipped with SP and NKA receptors and SP has been shown to induce the release of IL-1, IL-6 and TNF-␣ from these cells. 48,49 SP has also been reported to promote inflammatory cell chemotaxis, 50 fibroblast proliferation 51 and antibody formation. 52 Furthermore, it has been shown that SP enhances the secretion of prostaglandin E 2 and collagenase in synoviocytes 53 and that CGRP stimulates lymphocyte proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…22 blasts, lymphocytes and macrophages are equipped with SP and NKA receptors and SP has been shown to induce the release of IL-1, IL-6 and TNF-␣ from these cells. 48,49 SP has also been reported to promote inflammatory cell chemotaxis, 50 fibroblast proliferation 51 and antibody formation. 52 Furthermore, it has been shown that SP enhances the secretion of prostaglandin E 2 and collagenase in synoviocytes 53 and that CGRP stimulates lymphocyte proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the actions on the microcirculation, several recent investigations have provided evidence that neuropeptides can influence the activities of diverse inflammatory and immunocompetent cells through receptor-mediated mechanisms (reviewed by Eglezos et al, 1991;McGillis et al, 1991). SP in general acts as an immunostimulatory agent.…”
Section: Dense Sensory Innervationmentioning
confidence: 99%
“…SP plays an important role in the regulation of several immune responses. Both in vivo and in vitro studies have indicated that SP stimulates macrophage phagocytosis (Hartung et al, 1986), and T and B lymphocyte proliferation and effector functions (Eglezos et al, 1991).…”
Section: Glutathione and Lipid Peroxides Content In Hepatic Tissuementioning
confidence: 98%